Relation of atrophic gastritis with Helicobacter pylori-CagA(+) and interleukin-1 gene polymorphisms - Sierra, Rafaela (The WJG Press and Baishideng, 2008)
AIM: To determine the association of Helicobacter pylori (H pylori) CagA(+) infection and pro-inflammatory polymorphisms of the genes interleukin (IL)-1RN and IL-1B with the risk of gastric atrophy and peptic ulcers in a dyspeptic population in Costa Rica, a country with high incidence and mortality of gastric cancer. METHODS: Seven biopsy specimens, a fasting blood sample and a questionnaire concerning nutritional and sociodemographic factors were obtained from 501 consecutive patients who had undergone endoscopy for dyspeptic symptoms. A histopathological diagnosis was made. Pepsinogen concentrations were analyzed by enzyme linked immunosorbent assay (ELISA). Infection with H pylori CagA(+) was determined by serology and polymerase chain reaction (PCR). IL-1B and IL-1RN polymorphisms genotyping was performed by PCR-restriction fragment length polymorphism (PCR-RFLP) and PCR respectively. RESULTS: In this dyspeptic population, 86% were H pylori positive and of these, 67.8% were positive for CagA. Atrophic antral gastritis (AAG) was associated with CagA(+) status [odd ratio (OR) = 4.1; P < 0.000] and fruit consumption (OR = 0.3; P < 0.00). Atrophic body gastritis (ABG) was associated with pepsinogen PGI/PGII < 3.4 (OR = 4.9; P < 0.04) and alcohol consumption (OR = 7.3; P < 0.02). Duodenal ulcer was associated with CagA(+) (OR = 2.9; P < 0.04) and smoking (OR = 2.4; P < 0.04). PGI < 60 μg/L as well as PGI/PGII < 3.4 were associated with CagA(+). CONCLUSION: In a dyspeptic population in Costa Rica, H pylori CagA(+) is not associated with ABG, but it is a risk factor for AAG. The pro-inflammatory cytokine polymorphisms IL-1B + 3945 and IL-1RN are not associated with the atrophic lesions of this dyspeptic population.